Role of anatomical variations in chronic rhinosinusitis on diagnostic nasal endoscopy and computed tomography scan of paranasal sinuses - Parmar, Falguni J.; Patel, Avani D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Diagnostic nasal endoscopy (DNE) and computed tomography (CT) of para nasal sinuses play an important role in the diagnosis and treatment of chronic rhinosinusitis (CRS). The aim and objective of the study is to see the anatomical variations of the sinonasal region in CRS on DNE and CT paranasal sinuses (PNS). Methods: A descriptive type retrospective study of 30 patients attending the ENT outpatient department of our tertiary care center clinically diagnosed as CRS with symptoms persisting for 12 weeks or more, along with previously failed medical management, including topical nasal steroids, systemic decongestant and extended courses of antibiotics and who were willing to undergo endoscopic sinus surgery are included. Results: Majority of the patients had septal deviation either an anterior or posterior deviation but majority of the cases are asymptomatic for the deviation. Anatomical variations of uncinate process, middle turbinate, inferior turbinate, frontal recess, agger nasi cells, haller cells were studied as well. Conclusions: Prolonged duration of rhinosinusitis symptoms (more than 8-12 weeks) is the primary reason to evaluate a patient for CRS and making the choice between CT PNS or DNE is patient and disease dependent. Understanding the advantages and disadvantages of each helps us realize that they are of synergistic in nature and not competitive.